Karakterisasi Potensi dan Komponen Pembatas pada Biji Sorghum Lokal Varietas Coklat sebagai Tanaman Pangan ( Characterisation of Potential and Limiting Factors of Locally-Grown Brown Sorghum as Staple Food) - Erni Sofia Murtini; Ahmad Subagio; Sudarminto Setyo Yuwono; Irawan Setya Wardhana; Sulthon Fathoni (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Brown sorghum is one of cereals with high prospective to be developed as a new source of staple food in Indonesia because it is easily cultivated and has high productivity. However, this grain has been overlooked because of limited available information of its potential used. Aims of this research are to evaluate the sorghum grain to comprehensibly obtain the basic information of its potential and limited factors as staple food. Research results that locally grown brown sorghum grain obtained from Grati, Pasuruan had a high milling yield (77.99±1.39%). The polished grain was composed by 79.40±4.63% starch and 10.62±0.01% protein. It indicated that this sorghum grain was highly prospective to be developed as a staple food. However, the grain also had some restrictive factors such as tannin (8.83±0.05 mg/g), phytic acid (1.80±0.47 mg/g) and anti-trypsin (17.18±2.38 unit/g). The main fraction of protein sorghum grain was Kafirin where this fraction contains a high disulphide bond (550.43±4.92 µmol/g). Bioavailability of protein sorghum evaluated by in vivo and in vitro methods were 51% and 48.45%, respectively. These values could be considered as low digestibility. The sorghum grain had dimension of 3.9±0.7 mm length, 3.2±0.2 mm width and 1.8±0.01 mm thick. Polishing of sorghum grain using rice polished machine could not effectively removed the testa layer due to different dimension of both sorghum and rice grain. This result suggests that appropriate assembly of equipment to effectively polish sorghum grain is needed. Presence of the anti- nutritional compounds and the low digestibility of protein sorghum prove that the brown sorghum grains require further processing technology such as fermentation to be more suitable as a staple food. ABSTRAKSorghum coklat merupakan biji-bijian yang potensial dikembangkan menjadi tanaman pangan di Indonesia. Kelebihan tanaman ini adalah kemudahannya untuk dibudidayakan dan produktivitas yang tinggi. Namun keterbatasan informasi tentang potensinya, membuat biji sorghum kurang diperhatikan. Tujuan Penelitian ini adalah untuk mendapatkan informasi dasar tentang potensi dan pembatas biji sorghum lokal varietas coklat sebagai tanaman pangan. Penelitian dilakukan dengan menganalisa biji sorghum yang telah disosoh dengan penyosoh beras 4 kali. Hasil penelitian menunjukkan biji sorghum lokal varietas coklat yang didapatkan dari Grati Pasuruan ini cukup berpotensi sebagai tanaman pangan. Biji sosoh mempunyai kadar pati 79,40±4,63% dan protein yang tinggi yaitu 10,62±0,01%, selain itu rendemen sosoh juga tinggi mencapai 77,99±1,39%. Namun demikian, sorghum mengandung senyawa antigizi seperti tanin yang mencapai 8,83±0,05 mg/g, senyawa fitat 1,80±0,47 mg/g dan antitripsin 17,18±2,38 unit/g. Protein sorghum didominasi (71,40±1,29%) oleh kafirin yang memiliki ikatan disulfit tinggi (550,43±4,92 µmol/g). Daya cerna protein sorghum tergolong rendah terlihat dari uji secara in vivo 0,51 atau 51% dan in vitro dengan enzim tripsin sebesar 48,45%. Dimensi biji sorghum dengan rata-rata 3,9±0,7 mm panjang, 3,2±0,2 mm lebar dan 1,8±0,01 mm tebal berbeda dengan biji beras sehingga kurang cocok bila dilakukan penyosohan dengan penyosoh beras. Kandungan senyawa antigizi yang cukup tinggi dan keberadaan ikatan disulfit yang cukup besar serta ditunjang oleh daya cerna protein yang rendah, menunjukkan biji sorghum perlu penanganan lanjutan misalnya dengan proses fermentasi untuk meningkatkan potensinya sebagai bahan pangan.